Avramenko О. System approach as necessities condition quality of the technological formation - Авраменко, О. Б. (Pedagogy of Higher and Secondary Education, 2012)
Avramenko О. System approach as necessities condition quality of the technological formation. In article is presented history, philosophical-methodological analysis of the formation to theories of the designing the pedagogical systems and system approach as one of the main of the directions to methodologies of the special scientific cognitions, purpose and problem which consist in study determined object as complex systems.